STUDENTS’ DIFFICULTIES IN ENGLISH SPEAKING CLASS - Novita Ika Indriyani (Universitas Madura, 2020)
This study aim to answer: (1) What are of student’s difficulties and possible solution in English speaking at the ninth years grade of SMPI AL-KAROMAH SAMPANG? (2) What factors are causing student’s difficulties in English speaking at the ninth years grade of SMPI AL-KAROMAH SAMPANG?. The research design of this study is descriptive qualitative. The writer uses interview and observation as instrument of data. In this research, the researcher uses non participant observation, the writer only becomes an observer. The writer had taken part in class being observed. While participating as an observer, the writer observes what kinds of students’difficulties in English speaking and what are the causing factors students’ difficulties in English speaking. From the result of the observation, interview, and questionnaire the researcher concluded that most of the student at the ninth grade of SMPI Al-Karomah Sampang got difficulties in English speaking class here was caused by fear of mistakes, shyness, lack of motivation, and lack of confidence. And some of these factors are related to the learners themselves, the teaching strategies, the curriculum, and the environment.